Case Report on Hypophosphatemic Rickets: Life Sciences -Paediatrics - Bragadeeshwaran, N.; Vindhya; Somasekar (International Journal of Life Science and Pharma Research, 2023)
In children with rickets, osteoid fails to mineralize. This condition is sometimes accompanied by a vitamin D deficiency or a drop in blood phosphate levels, which causes hypophosphatemia. This case report describes a 4-year-old youngster with persistent respiratory conditions since he was nine months old. At an outpatient tubulopathies clinic, throughout a 24-month study, information on the patient's metabolic profile, creatinine clearance, nutritional status, weight, and body composition was gathered. Clinical and laboratory evidence of hypophosphatemia rickets was present in the patient. The patient's bone metabolism had changed. He had been bedridden for some time and was mechanically ventilated. Our case improved after receiving phosphate, calcium, and calcitriol multiple as treatment. The patient improved, eventually walking alone and breathing on his own. Additionally, weight and structural development are enhanced with transient gallstones. The clearance of creatinine was constant. The medication improved his test results and nutritional status. Following two years of treatment, he fully recovered. Early detection can help kids receive additional support earlier and prevent them from falling behind. All age groups can benefit from multimodality treatment, which is essential for managing the condition. The current example is presented since it is so uncommon.